Dietary strategies to reduce environmental impact must be nutritionally complete. (20th May 2017) - Ridoutt, Bradley; Hendrie, Gilly; Noakes, Manny
Highlights: Sustainable diets must be nutritionally complete. Low environmental impact diets should not risk inadequate micronutrient intake. Discretionary foods contribute little to nutrition. Discretionary foods contribute to the problem of excess energy intake. Discretionary foods inflate environmental burdens of diets.